KEKERASAN GENDER PADA TOKOH UTAMA DALAM CERPEN KALI KETIGA INI NINGSIH MELAHIRKAN BAYI KARYA SUSANTO ABOGE - Restiawati, Defi; Irma, Cintya Nurika (University of Brawijaya, 2024)
This study aims to describe the existence of gender injustice in this third time Ningsih gave birth to a baby (Kali Ketiga Ini Ningsih Melahirkan Bayi) by Susanto Aboge. This type of research uses qualitative descriptive methods with the object of research into the form of gender violence experienced by the main character in this third-time short story Ningsih Giving Birth to a Baby by Susanto Aboge using a feminism approach. The source of this research data is the third time Ningsih Ningsih Gave Birth to a Baby by Susanto Aboge which was accessed online in ruangsastra.com published in 2021. The data analysis technique in this study is to read the short story over and over again until it understands describing and drawing conclusions. The results of this study are decied through words and sentences contained in short stories. From the short story This time Ningsih Gave Birth to a Baby by Susanto Aboge found three forms of violence in the main character, namely (1) physical violence felt directly by the main character named Ningsih carried out by two nurses by tying his hands because of mental illness that in Ningsih (2) psychological violence against Ningsih was carried out by Kaji Bakir who did not approve of his romance because he considered Ningsih was a descendant of a PKI , and (3) the sexual violence that occurred against Ningsih was the third time she conceived without a husband because of irresponsibility.